(untitled) (Bangladesh Journal of Medical Science, 2017)
Objective: This study was designed to compare the level of apical microleakage of root canal sealers; Acroseal, AH Plus, Endoflas FS and Endomethasone N, with laterally condensed gutta percha by level of apical dye penetration. Materials and Methods: Freshly extracted sixty permanent maxillary anterior teeth were divided randomly into four groups. Shaping and cleaning of teeth was done followed by obturation with gutta percha and four different root canal sealers. Samples were immersed in 2% methylene blue dye solution in individual dappen dish and stored in the solution for 30 days. The roots were split longitudinally with a chisel in two halves and observed under stereomicroscope. Apical microleakage measured from the apex to the most coronal extent of dye penetration. Results: Minimum microleakage was observed with AH Plus with mean value 2.140 mm, standard deviation 0.817. The maximum microleakage was observed with Endomethasone N with mean value 3.858 mm, standard deviation 1.840. There was no statistically significant difference in microleakage between Acroseal, AH Plus, and Endoflas FS. Endomethasone N showed highest level of microleakage than other three groups under the test condition, which was statistically significant. Conclusion: The microleakage was the lowest for the AH Plus and increased in the following order, Endoflas FS, Acroseal, Endomethasone N. Bangladesh Journal of Medical Science Vol.16(2) 2017 p.219-224